Effect of Current Ratio, Debt to Equity Ratio, and Return on Assets on Stock Prices of Property and Real Estate Companies on the Indonesia Stock Exchange (2018-2023) - Gina Ismatul Asna; Erna Herlinawati (CV. Publikasi Indonesia, 2024)
This research aims to analyze the impact of the CR, DER and ROA on stock prices of companies in the property and real estate sector listed on the IDX during the 2018-2023 period. The data used in this research were collected through documentation methods by accessing the companies' annual financial reports published on the Indonesia Stock Exchange. Using multiple linear regression analysis, the study found that the current ratio and debt-to-equity ratio do not have a significant impact on stock prices. On the other hand, return on assets was found to have a significant impact on stock prices. The results of this study indicate that investors pay more attention to the profitability of companies, as reflected in the return on assets, rather than liquidity or capital structure when determining stock values in the property and real estate sector.